RADIATION TREATMENT OF UNRESECTABLE LARYNGEAL CANCER - K. B. Gordon; I. A. Gulidov; V. A. Rozhnov; V. G. Andreev; N. I. Podlesnykh; V. A. Pankratov (Сибирский онкологический журнал, 2016)
The treatment outcomes of unresectable laryngeal cancer have been presented. The techniques of radiation therapy (RT) alone and concurrent chemoradiotherapy (CRT), as well as the effect of changes in the fractionation regimens on the treatment outcome have been analyzed. No differences in overall survival (OS) and locoregional control (LC) between the RT and CRT techniques were found (p<0.8). There is a trend toward improvement in OS (p<0.1) and LC (p<0.05) in laryngeal cancer patients treated with hyperftactionated radiation therapy.